Sabbath Observance: Social Analysis in the Context of Community Welfare - Antonius Dwiky Mulyono; Alvyn C. Hendriks (Syntax Idea)
Discusses the importance of Sabbath observance in both social and spiritual contexts. Sabbath, the day of rest ordained by the Law of God, provides time for humans to rest, worship, and connect with others. The practice of Sabbath observance not only holds spiritual implications but also economic and social ones. Sabbath observance restricts economic activities, thus aiding in reducing social disparities temporarily. Furthermore, Sabbath strengthens brotherhood and unity within communities. The concepts of the Sabbatical Year and the Year of Jubilee also bring forth positive social implications, including debt release and emancipation of slaves, providing opportunities for the less fortunate. Hence, Sabbath observance has a positive impact on societal well-being